I, robot : to protect - Reichert, Mickey Zucker (ROC, 2011)
"2035: Robotic technology has evolved into the realm of self-aware, sentient mechanical entities. The future of the human race is to be inevitably linked with its most brilliant creation. But there are some who do not want the future to arrive.... Intelligent and driven, Dr. Susan Calvin is beginning her residency in psychiatry at Manhattan Hasbro teaching hospital, where a select group of patients is receiving the latest in diagnostic advancements--nanotechnology ... But what no one knows is that a technology that promised to improve life is now under the control of those who seek to spread only death..."--